2013
DOI: 10.1002/ajhb.22429
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for novel genetic loci associated with metabolic traits in Yup'ik people

Abstract: Objectives: To identify genomic regions associated with fasting plasma lipid profiles, insulin, glucose, and glycosylated hemoglobin in a Yup’ik study population, and to evaluate whether the observed associations between genetic factors and metabolic traits were modified by dietary intake of marine derived omega-3 polyunsaturated acids (n-3 PUFA). Methods: A genome-wide linkage scan was conducted among 982 participants of the Center for Alaska Native Health Research study. n-3 PUFA intake was estimated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
(41 reference statements)
0
12
0
Order By: Relevance
“…However, as a validated biomarker of marine food (fish and marine mammal) intake for the Yup’ik population of SW Alaska, the RBC δ 15 N value has been used to examine how gene × diet interactions are associated with risk factors for obesity and chronic disease (2, 71, 81, 82), and it was recently used to demonstrate that high and low consumers of marine foods exhibit very different patterns of gene methylation (3). We found that the RBC δ 15 N value captured most of the same diet - risk factor associations that were previously identified for Yup’ik people using RBC EPA and DHA (84), but that in addition, high RBC δ 15 N values were associated with high adiponectin, which promotes insulin sensitivity, and were inversely associated with blood pressure (102).…”
Section: Stable Isotope Ratios In Human Dietary Studiesmentioning
confidence: 99%
“…However, as a validated biomarker of marine food (fish and marine mammal) intake for the Yup’ik population of SW Alaska, the RBC δ 15 N value has been used to examine how gene × diet interactions are associated with risk factors for obesity and chronic disease (2, 71, 81, 82), and it was recently used to demonstrate that high and low consumers of marine foods exhibit very different patterns of gene methylation (3). We found that the RBC δ 15 N value captured most of the same diet - risk factor associations that were previously identified for Yup’ik people using RBC EPA and DHA (84), but that in addition, high RBC δ 15 N values were associated with high adiponectin, which promotes insulin sensitivity, and were inversely associated with blood pressure (102).…”
Section: Stable Isotope Ratios In Human Dietary Studiesmentioning
confidence: 99%
“…Intakes of EPA and DHA are high and quite variable in YupÕik people (6); therefore, associations with health are of particular interest for further study (8)(9)(10)(11). Because d 15 N is relatively simple and inexpensive to assay, several recent studies have used d 15 N as a surrogate measure of n-3 PUFA intake (10,12,13). However, EPA and DHA derive from marine fats, whereas elevated d 15 N derives from marine protein, and these components are sometimes rendered and eaten separately (e.g., as seal oil and seal meat).…”
Section: Introductionmentioning
confidence: 99%
“…Detailed descriptions of the genotyping procedures and data cleaning of CANHR Yup’ik samples have also previously been published [26]. Briefly, we used the Illumina Linkage IV panel to genotype 6090 SNPs spanning the entire genome, with an average genetic distance of 0.58 cM.…”
Section: Methodsmentioning
confidence: 99%